ANALISIS IMPLEMENTASI HALAL VALUE CHAIN TERHADAP PENINGKATAN KUALITAS PRODUK USAHA KATERING DI KECAMATAN TARIK KABUPATEN SIDOARJO - Al Mubarok, Roifi; Abidah Suryaningsih, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of the halal value chain in catering businesses is important toensure halal products and improve product quality. This study aims to analyze the implementation of the halal value chain, its supporting and inhibiting factors, and its impact on product quality in catering businesses in Tarik District, Sidoarjo Regency. This research used a descriptive qualitative approach based on the halal value chain theory and the concept of product quality. Data were collected through observation, semi-structured interviews, and documentation, then analyzed usingdata reduction, data presentation, and conclusion drawing with triangulation for data validity. The findings show that the halal value chain has been implemented in raw material selection, production, storage, and distribution. Supporting factors include business owners' awareness, assistance from Halal Product Process Assistants (PPH), and increasing demand for halal products, while the main obstacles are limited understanding and business documentation. The implementation of the halal value chain contributes to improving hygiene, safety, product consistency, and consumer trust.